2013
DOI: 10.1093/jpepsy/jst023
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing to Enhance Self-Efficacy and Promote Weight Loss in Overweight and Obese Adolescents: A Randomized Controlled Trial

Abstract: Health benefits from participation in individual therapy may have been accrued; however, specific benefits attributable to MI were limited. Findings suggest that more than one type of counseling intervention (i.e., MI and social skills training) may be beneficial when providing integrative treatment for obese youth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 22 publications
4
55
1
6
Order By: Relevance
“…Several studies examined the use of MI as an adjunctive to standard treatments, with no differences found between MI-enhanced FBT to standard FBT (Saelens, Lozano, & Scholz, 2013) or social skills training (Walpole, Dettmer, Morrongiello, McCrindle, & Hamilton, 2013), improved vegetable intake compared to standard Women, Infants, and Children nutritional counseling (Ogu et al, 2014), and improved physical activity outcomes at 6-month followup compared to a standard cognitive-behaviorally based weight loss program (Gourlan, Sarrazin, & Trouilloud, 2013). These results suggest that MI may be a viable addition to well-established treatments and additional research is needed and warranted.…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…Several studies examined the use of MI as an adjunctive to standard treatments, with no differences found between MI-enhanced FBT to standard FBT (Saelens, Lozano, & Scholz, 2013) or social skills training (Walpole, Dettmer, Morrongiello, McCrindle, & Hamilton, 2013), improved vegetable intake compared to standard Women, Infants, and Children nutritional counseling (Ogu et al, 2014), and improved physical activity outcomes at 6-month followup compared to a standard cognitive-behaviorally based weight loss program (Gourlan, Sarrazin, & Trouilloud, 2013). These results suggest that MI may be a viable addition to well-established treatments and additional research is needed and warranted.…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…23 Although meta-analytical differences in effect sizes favor parental involvement, no existing RCT studies compare .2 of the 3 target groups (eg, MI, MI + PI, control) in the same trial experimentally. 23,[27][28][29] The goal of the present RCT was to evaluate the effectiveness of an MI weight loss intervention for obese adolescents including parental involvement (MI + PI) versus MI without parental involvement (MI only) and a passive control group over a period of 12 months. We hypothesized that MI + PI would be effective in changing BMI and other relevant outcomes compared with a control condition.…”
Section: What This Study Addsmentioning
confidence: 99%
“…The US Preventive Services Task Force recommends screening children aged $6 years for obesity and referring to behavioral interventions. The task force found that effective comprehensive weight-management programs incorporated counseling and other interventions that targeted diet and PA. 20 Despite the strength of the recommendations in guidelines, 15,20 many studies found small or no impact of motivational interviews (MIs) on BMI on overweight [21][22][23][24][25][26][27] or on obese children. [28][29][30] Therefore, it is still necessary to test the effectiveness of the interventions in any context, when possible by using randomized controlled trials.…”
mentioning
confidence: 99%